Concept of Islamic Education Curriculum: A Study on Moral Education in Muhammadiyah Boarding School, Klaten - Fatimah, Meti (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
This study discusses the concept of moral education. The goals of moral education are: 1) learn the concept of moral education curriculum; 2) the process of internalizing moral education. This study uses a qualitative approach with phenomenological method. The results show that, first: moral education must be based on the concept of Islam and placing morals in science is a shared responsibility because it includes doctrinal implications that the purpose of human life must be within the framework of worship of God. Second: Muhammadiyah Islamic Boarding School makes morality the basis of education with an internalization process including integrating general and religious subject curricula, habituation methods and 3T programs, namely tahfizh (memorizing), tafhim (understanding) and taf'il (practice).